Prevalence of secondhand smoke exposure in asthmatic children at home and in the car: A cross-sectional study - Antunes, H (2016)
OBJECTIVE: To compare secondhand smoke exposure (SHSe) prevalence at home and inside the car between asthmatic and non-asthmatic Portuguese children. MATERIALS AND METHODS: This is a cross-sectional study that assessed children's SHSe in a representative sample of nine Portuguese cities. A validated self-reported questionnaire was administered to a random sample of 4th grade students during the school year of 2010/2011. The asthma prevalence was defined by the answers to three questions regarding asthma symptoms, medication and inhaler use. We performed chi-square tests and analysed frequencies, contingency tables, confidence intervals, and odd-ratios. RESULTS: The self-reported questionnaire was administered to 3187 students. Asthma prevalence was 14.8% (472 students). Results showed that 32.3% of non-asthmatic children and 32.4% of asthmatic children were exposed to secondhand smoke as at least one of their household members smoked at home. The prevalence of parental smoking, smoking among fathers and smoking among mothers at home was also similar in both groups (asthmatic and non-asthmatic children). SHSe inside the car was 18.6% among non-asthmatic children and 17.9% among asthmatic children. CONCLUSIONS: Asthmatic and non-asthmatic children were equally exposed to secondhand smoke, because no significant differences were found between the two groups concerning the prevalence of SHSe at home and inside the car. These findings highlight the need to include SHSe brief advice in paediatric asthma management.